Photodissociation dynamics of water molecule at short photon wavelengths: full dimensional potential energy surface of Rydberg states. (25th June 2021) - Peng, Yigeng; Hu, Xiaoqing; Wu, Yong; Wang, Jianguo; Lu, Ruifeng; Sisourat, Nicolas
Abstract: In this work, we have combined the multi-reference double-excitation configuration interaction method, developed by Buenker and Peyerimhoff (1974 Theor. Chim. Acta 35 33), with molecular orbitals optimized with a multi-configurational self-consistent-field approach. Using the example of the water molecule, we show that such a combined technique lowers the computational costs while improving the overall accuracy, especially for highly excited states. With this new approach, we have computed the full-dimensional potential energy surfaces (PESs) of water molecule up to the F ̃ states. Furthermore, using these PESs we study the photodissociation dynamics of water triggered with short wavelength photons, which have been investigated in recent free electron laser experiments. Our results indicate new and eﬀicient fragmentation pathways. This work paves the way to the study of reaction dynamics of polyatomic molecules in high-lying electronic states.